2003
DOI: 10.1892/0891-6640(2003)17<238:csiaas>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium sordelli Infection as a Suspected Cause of Transient Hyperammonemia in an Adult Horse

Abstract: A 5-year-old Dutch Warmblood gelding was referred to the University of Pennsylvania George D. Widener Hospital for the evaluation of abdominal discomfort and acute onset of neurologic deficits. The horse was imported from Holland 10 days before admission and was intended to be used for dressage. Vaccination for rhinopneumonitis, influenza, and tetanus was performed 11 months before importation, and the horse had no medical history that was relevant to this study. The day before presentation, the horse was depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(56 citation statements)
references
References 6 publications
1
55
0
Order By: Relevance
“…Bacteria that produce ammonia in the gastrointestinal tract are gram‐negative aerobic bacilli, such as Escherichia coli , Klebsiella , Proteus , and Pseudomonas 3. Clostridium sordelli is a gram‐positive spore‐forming bacillus that also has been implicated as a potential cause of hyperammonemia associated with colitis in the horse because of its urease activity 1. Salmonella agona , the bacterium isolated in this case, is not known to be a urease‐producing bacterium 8…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Bacteria that produce ammonia in the gastrointestinal tract are gram‐negative aerobic bacilli, such as Escherichia coli , Klebsiella , Proteus , and Pseudomonas 3. Clostridium sordelli is a gram‐positive spore‐forming bacillus that also has been implicated as a potential cause of hyperammonemia associated with colitis in the horse because of its urease activity 1. Salmonella agona , the bacterium isolated in this case, is not known to be a urease‐producing bacterium 8…”
Section: Discussionmentioning
confidence: 96%
“…Hyperammonemia in the absence of liver disease has been reported as a cause of encephalopathy in 11 horses, 9 of whom had signs of gastrointestinal disease 1–7. The majority of these horses were either euthanized, or died shortly after developing signs of encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sordellii is a soil organism and is able to penetrate the wounds and mucous membranes. It has been demonstrated that C. sordellii induces haemorrhagic enteritis in equine neonates and oedema, infection of wounds and hyperammonemia in adult horses (Desrochers et al, 2003;Ortega et al, 2007). C. perfringens is a life-threatening bacterium in 1-10 day old foals, inducing necrotizing enterocolitis (East et al, 1998).…”
Section: Discussionmentioning
confidence: 99%